Maternal dietary fiber intake during pregnancy and child development: the Japan Environment and Children's Study - Miyake, Kunio; Horiuchi, Sayaka; Shinohara, Ryoji; Kushima, Megumi; Otawa, Sanae; Yui, Hideki; Akiyama, Yuka; Ooka, Tadao; Kojima, Reiji; Yokomichi, Hiroshi; Mochizuki, Kazuki; Yamagata, Zentaro; et al. (Frontiers in Nutrition, 2023)
Background: Animal studies have shown that maternal low-fiber diets during pregnancy may impair brain development and function in offspring, but this has not been validated by epidemiological studies. The aim of this study was to investigate the link between maternal dietary fiber intake during pregnancy and neurodevelopmental delay in offspring using a large birth cohort. Methods: A total of 76,207 mother-infant pairs were analyzed using data from the Japan Environment and Children’s Study, a nationwide prospective cohort study. Maternal dietary fiber intake was estimated using the food frequency questionnaire in mid-pregnancy. Maternal dietary fiber intake was adjusted for energy and classified into quintiles. Developmental delay was assessed in five domains using the Japanese version of the Ages and Stages Questionnaire, Third Edition at the age of 3 years. The logistic regression analysis was performed to estimate the odds ratio (OR) and 95% confidence interval (CI) for the link between dietary fiber intake during pregnancy and developmental delay at the age of 3 years. Results: The lowest intake group of total dietary fiber had a higher risk of delayed communication (adjusted OR [aOR], 1.51; 95% CI, 1.32–1.74), fine motor (aOR, 1.45; 95% CI, 1.32–1.61), problem-solving (aOR, 1.46; 95% CI, 1.32–1.61), and personal-social skills (aOR, 1.30; 95% CI, 1.12–1.50) than did the highest intake group. An analysis that excluded the effects of insufficient folic acid intake during pregnancy also showed a similar trend. Conclusion: This study showed that maternal dietary fiber deficiency during pregnancy might influence an increased risk of neurodevelopmental delay in offspring.